PERAN PERSEPSI DALAM KEPUTUSAN KONSUMEN MENGGUNAKAN VAKSIN COVID-19 (The Role of Perception in Consumer Decisions to Use The Covid-19 Vaccine) - Hartini Hartini; La Janu La Janu; Risky Tamala (Pascasarjana Universitas Halu Oleo, 2022)
This study aims to determine the role of perception in consumer decisions to use the Covid-19 vaccine. The unit of analysis in this study was Halu Oleo University students, with a total of 30 informants who were determined by accidental sampling technique. Data was collected through observation and interviews, and then analyzed inductively. The results of the study show that perceptions of the Covid-19 vaccine play a role in consumers' decisions to use the Covid-19 vaccine..